Risk management model and its impact on the scope, time and cost of basic sanitation projects, case Tacna, 2017 - Quevedo Porras, Violeta Zarela (2020)
Infrastructure projects incorporate, as a general rule, a complex contractual structure that must respond to the needs of the project, including the risk management in the construction of the works.The objective is to develop a risk management model that improves the scope, time and cost of the direct management basic sanitation projects executed by the EPS of the Tacna Region, 2017. For this purpose, the research used is of the application type. , not experimental and quantitative. Determine the specific objectives through tools and techniques, through surveys and expert evaluation, which are processed with the Monte Carlo Method using the RiskyProject Professional Program that records the risks that are part of the scope, determines the contingency in cost and time.The risk management model to be followed responds to the good practices of the PMBOK. The application of the proposed model improves the execution of basic sanitation projects in the Tacna Region, allowing compliance with the scope, deadline, economic profitability and sustainable development.